A Modified mRNA Vaccine Targeting Immunodominant NS Epitopes Protects Against Dengue Virus Infection in HLA Class I Transgenic Mice - Roth, Claude; Cantaert, Tineke; Colas, Chloé; Prot, Matthieu; Casadémont, Isabelle; Levillayer, Laurine; Thalmensi, Jessie; Langlade-Demoyen, Pierre; Gerke, Christiane; Bahl, Kapil; Ciaramella, Giuseppe; Simon-Loriere, Etienne; et al. (Frontiers in Immunology, 2019)
Dengue virus (DENV) induces strong T and B cell responses upon infection. Hence, it is difficult to determine the contribution of cell-mediated immunity alone in the long lasting protection against DENV infection and disease. Numerous CD4+ and CD8+ T cell epitopes have been identified, mainly in the non-structural proteins of DENV. Taking into account the immunogenicity and peptide sequence conservation among the different DENV serotypes, a minimal DENV antigen, called DENV1-NS, has been designed. This antigen is enriched in conserved and highly antigenic epitopes located in the NS3, NS4B and NS5 regions of DENV1. To evaluate the ability of the DENV1-NS poly-epitope to express the antigenic peptides in the context of different HLA class I molecules, we established its in vivo immunogenicity by measuring, after DNA immunization and electroporation, the activation of DENV-specific CD8 T cells in transgenic mice expressing the human HLA-A*0201, -A*2402, -B*0702 and -B*3502 class I alleles. We then engineered a lipid nanoparticle (LNP) encapsulated modified mRNA vaccine encoding DENV1-NS and tested immunogenicity and protection in these human HLA class I transgenic mice, after transient blockade of the interferon (IFN) type I receptor. Significant protection was observed, after two injections of the modified mRNA vaccine. Collectively, these data strongly support the development of T cell-based vaccines targeting immunodominant T cell epitopes that generate potent virus-specific T cell responses conferring immunity against DENV infection.